Implementasi K3 pada Proses Welding di PT Chandra Nugerah Cipta Menggunakan Metode HIRARC - Rahman, Andhika Nur; Fitra, Adi; Intani, Arvita Emarilis (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Welding is one of the high-risk work activities in the manufacturing industry, including at PT Chandra Nugerah Cipta. This study aims to identify potential hazards, assess risk levels, and provide technical recommendations to reduce the risk of work accidents in the welding area using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. The research was conducted qualitatively through observation, interviews, and documentation. The results identified 20 potential hazards, categorized into 4 extreme risks (20%), 5 medium risks (25%), and 11 low risks (55%). After implementing risk controls through engineering controls, administrative controls, and the provision of personal protective equipment (PPE), the number of work accidents decreased by 64% within three months. The HIRARC method proved effective in improving workplace safety and fostering a safer work culture.